The effect of multiple doses of ubrogepant on the pharmacokinetics of an oral contraceptive in healthy women: Results of an open-label, single-center, two-period, fixed-sequence study - Chi-Chung Li; John Palcza; Jialin Xu; Bob Thornton; Wendy Ankrom; Abhijeet Jakate; Eugene E Marcantonio (SAGE Publishing, 2020)
Background: Ubrogepant is a novel, oral calcitonin gene-related peptide receptor antagonist for acute treatment of migraine. This study evaluated potential drug-drug interactions between ubrogepant and an oral contraceptive containing ethinyl estradiol (EE) and norgestimate (NGM). Methods: This open-label, single-center, two-period, fixed-sequence study enrolled healthy, postmenopausal or oophorectomized, adult women. In period 1, participants received a single oral dose of EE 0.035 mg/NGM 0.25 mg (EE-NGM) followed by a 7-day washout. In period 2, participants received oral ubrogepant 50 mg daily on days 1-14; single-dose EE-NGM was coadministered with ubrogepant on day 10. Pharmacokinetic parameters for plasma EE and norelgestromin (NGMN) were compared with and without ubrogepant. Results: Twenty-two participants aged 46-66 years were enrolled; 21 completed the study. Geometric mean ratios and 90% confidence intervals for the comparison of EE-NGM + ubrogepant to EE-NGM alone were contained within 0.80 and 1.25 for area under the plasma drug concentration-time curve (AUC) from time zero to infinity (AUC 0-∞ ; 0.96 [0.91, 1.01]) and C max (0.91 [0.82, 1.004]) of NGMN and AUC 0-∞ (0.97 [0.93, 1.01]) of EE, but not C max of EE (0.74 [0.69, 0.79]). Median t max of EE was delayed following EE-NGM + ubrogepant (3.0 h) versus EE-NGM alone (median of 1.5 h), whereas median t max of NGMN was unchanged (1.5 h). Geometric mean apparent terminal half-life ( t ½ ) was similar with and without ubrogepant for EE (23 vs. 21 h) and NGMN (36 h both conditions). All ubrogepant-related adverse events were mild or moderate. Conclusion: Ubrogepant did not demonstrate potential for clinically meaningful drug-drug interactions with an EE-NGM oral contraceptive. Trial registration: Not applicable (phase 1 trial)